1999
DOI: 10.1677/joe.0.1620143
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for enhanced rates of complement activation in serum from patients with newly diagnosed insulin-dependent diabetes mellitus exposed to rat islet cells and complement-dependent induction of islet cell apoptosis

Abstract: In this paper we report the concentration of terminal complement complexes (TCCs, SC5b-9, an index of complement activation) in newly diagnosed insulindependent diabetes mellitus (IDDM) patient serum and normal human serum. In the nine patients studied, levels of serum soluble TCCs were approximately 1·6-fold higher than in sera obtained from normal control individuals. On incubation of rat islet cells with diluted serum (10%, v/v, concentration), complement activation was increased at a significantly faster r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
3

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 33 publications
1
13
0
3
Order By: Relevance
“…Complement activation and cellular attack is known to involve a rapid elevation of [Ca 2+ ] i within the target cell , Morgan & Campbell 1985, Newsholme et al 1993, 1999 which may result in induction of death via apoptosis or necrosis (JunttiBerggren et al 1993, Caraher et al 1999, or result in activation of recovery mechanisms (Morgan & Campbell 1985). Application of serum from Type-1 diabetic patients to rat islets and clonal -cells clearly results in complement activation and disturbances in insulin secretion (Conroy et al 2000 and references therein).…”
Section: Cell Deathmentioning
confidence: 99%
See 1 more Smart Citation
“…Complement activation and cellular attack is known to involve a rapid elevation of [Ca 2+ ] i within the target cell , Morgan & Campbell 1985, Newsholme et al 1993, 1999 which may result in induction of death via apoptosis or necrosis (JunttiBerggren et al 1993, Caraher et al 1999, or result in activation of recovery mechanisms (Morgan & Campbell 1985). Application of serum from Type-1 diabetic patients to rat islets and clonal -cells clearly results in complement activation and disturbances in insulin secretion (Conroy et al 2000 and references therein).…”
Section: Cell Deathmentioning
confidence: 99%
“…However, it is known that ATP concentration must fall substantially before apoptosis is triggered directly by this mechanism. For example, the concentration of ATP was reduced by 90-95% in rat islet cells incubated in Type-1 diabetic patient serum, before cell death occurred by apoptosis (Caraher et al 1999), while apoptosis was induced in insulin-producing pituitary cells overexpressing GLUT-2 and glucokinase after exposure to 20 mM glucose, a condition which also reduced ATP concentration by approximately 80% (Faradji et al 2001). The latter paper also reported a drop in ATP concentration of approximately 40% in cells overexpressing glucokinase only, after exposure to 20 mM glucose, a condition which did not result in apoptosis of the cells.…”
Section: Cell Deathmentioning
confidence: 99%
“…Other reports have described stimulation of insulin release from mouse islets by normal human serum (Idahl et al 1980) or inhibition of glucose-stimulated secretion of insulin from mouse islet cells incubated in the presence of heat-inactivated IDDM patient sera for 2 h and subsequently in the presence of guinea pig serum as a source of complement (Boitard et al 1981, Sensi et al 1985. However, we have demonstrated that rat islet cells incubated in the presence of 10% IDDM patient serum undergo morphological changes resulting in increased buoyant cell density (apoptosis-associated cell shrinkage) after 4 h (Caraher et al 1999), which may result in an inhibition of insulin secretion via a mechanism closely linked with the signal transduction pathways responsible for cell death.…”
Section: Discussionmentioning
confidence: 98%
“…3. We have previously shown that the concentration of SC5b-9 increased time-dependently in media supplemented with IDDM sera or normal human sera after exposure to rat pancreatic islets (Caraher et al 1999). Although culture medium supplemented with sera from some individual patients demonstrated substantially greater concentrations of SC5b-9 compared with the mean concentration in medium supplemented with normal human sera, overall, no statistically significant difference was found between media supplemented with IDDM patient sera or normal human serum (Mann-Whitney U-test).…”
Section: Sc5b-9 Production In Culture Media Of Clonal -Cells Exposedmentioning
confidence: 99%
“…The pancreatic islet is exposed to varying degrees of ischemic damage during organ procurement, islet isolation, and transplantation. This damage elicits several biochemical responses that lead to cell death [16,17], and involves a complex chain of events such as the depletion of energy substrates and production of reactive oxygen species (ROS) [18]. Due to low levels of antioxidant enzymes in the islet, the cellular stress response is of considerable relevance to islet survival in an inflammatory environment.…”
Section: Discussionmentioning
confidence: 99%